2020
DOI: 10.1161/circ.142.suppl_3.15990
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 15990: Incidence and Outcomes of Elevated Troponins in Patients With Rhabdomyolysis

Abstract: Introduction: The relationship between rhabdomyolysis and elevated troponins has not been clearly established. Literature has been limited to case reports and small single center studies. However, there are no studies that evaluated the incidence and outcomes of troponin elevation in patients with rhabdomyolysis. Methods: Patients of 18 years and older with rhabdomyolysis were selected from the Healthcare Cost and Utilization Project National Inpatient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Studies on the risks of elevated conventional Tn in rhabdomyolysis show mixed results regarding the increased risk of mortality, although a large study of 404,369 patients with rhabdomyolysis showed an increased risk of mortality and a higher hospital cost in patients with elevated Tn [ 219 , 222 ]. Treatment with fluid resuscitation has been found to reduce measured serum Tn levels to baseline, but patients at risk for CAD should undergo evaluation after the resolution of rhabdomyolysis [ 155 , 221 ].…”
Section: Non-cardiovascular Etiologies Of Troponin Elevationmentioning
confidence: 99%
“…Studies on the risks of elevated conventional Tn in rhabdomyolysis show mixed results regarding the increased risk of mortality, although a large study of 404,369 patients with rhabdomyolysis showed an increased risk of mortality and a higher hospital cost in patients with elevated Tn [ 219 , 222 ]. Treatment with fluid resuscitation has been found to reduce measured serum Tn levels to baseline, but patients at risk for CAD should undergo evaluation after the resolution of rhabdomyolysis [ 155 , 221 ].…”
Section: Non-cardiovascular Etiologies Of Troponin Elevationmentioning
confidence: 99%